2021
DOI: 10.1098/rspb.2020.3173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water content on mechanical behaviour of gastropod taenioglossan radulae

Abstract: One molluscan autapomorphy is the radula, the organ used for feeding. Here, for the first time, the performance and failure of taenioglossan radular teeth were tested in a biomechanical experiment which in turn allowed building hypotheses about tooth functionalities. Shear load was applied to tooth cusps with a force transducer until structural failure occurred, the broken area was measured, and finally breaking stress was calculated. These experiments were carried out under dry and wet conditions. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 61 publications
2
49
0
Order By: Relevance
“…Our results indicate that centrals are not affected by stress and strain, marginals are highly affected, and laterals are intermediate [55]. (v) By breaking stress experiments, documenting the force needed to break teeth, we found that centrals are capable of resisting the highest stresses, followed by the laterals, and finally marginal teeth [56,57]. During these experiments, we observed that native (wet) centrals and laterals can interlock with adjacent teeth and thus resist higher stresses (collective effect), whereas the wet (native) marginal teeth are capable of twisting and bending.…”
Section: Function Of Radular Partsmentioning
confidence: 62%
See 3 more Smart Citations
“…Our results indicate that centrals are not affected by stress and strain, marginals are highly affected, and laterals are intermediate [55]. (v) By breaking stress experiments, documenting the force needed to break teeth, we found that centrals are capable of resisting the highest stresses, followed by the laterals, and finally marginal teeth [56,57]. During these experiments, we observed that native (wet) centrals and laterals can interlock with adjacent teeth and thus resist higher stresses (collective effect), whereas the wet (native) marginal teeth are capable of twisting and bending.…”
Section: Function Of Radular Partsmentioning
confidence: 62%
“…By almost all manipulations of the model, we observed a tight interlocking and formation of a stiff array due to the interaction of the laterals, which is clearly a kind of 'collective effect' leading to a proper stress distribution and thus to the reduction of the structural failure, when interacting with ingesta (for stress distribution through the interlocking of teeth, see also [2,32,[56][57][58][59][60][61][62]). The centrals usually do not form a stiff array with the adjacent central teeth but enable the stabilization of each transversal tooth row by lateral interlocking with the lateral teeth.…”
Section: Function Of Radular Partsmentioning
confidence: 99%
See 2 more Smart Citations
“…We thus propose that specific cross-linking conditions of the chitin due to tanning 1 , fiber arrangement, and density 22 , 23 , 26 , 28 , 31 , 88 , 143 145 rather cause the heterogeneities in mechanical properties. We previously also detected that the capability of wet teeth to rely on one another and to redistribute the mechanical stress increases the radula’s resistance to structural failure in paludomid gastropods 146 , 147 . This altogether probably enables the feeding on harder ingesta types.…”
Section: Discussionmentioning
confidence: 90%